2021
DOI: 10.3390/ijms222312992
|View full text |Cite
|
Sign up to set email alerts
|

Sex Bias in Differentiated Thyroid Cancer

Abstract: Differentiated thyroid cancers are more frequent in women than in men. These different frequencies may depend on differences in patient’s behavior and in thyroid investigations. However, an impact on sexual hormones is likely, although this has been insufficiently elucidated. Estrogens may increase the production of mutagenic molecules in the thyroid cell and favor the proliferation and invasion of tumoral cells by regulating both the thyrocyte enzymatic machinery and the inflammatory process associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 173 publications
(235 reference statements)
2
43
1
1
Order By: Relevance
“…The results of one study confirm that patients with PTC with distant metastases have a good prognosis after treatment (Sampson et al, 2007). Another study found that sex is a prognostic factor for DTCDM, likely because estrogen production limits cancer progression (Suteau et al, 2021). The current study found that tumor size was an important factor affecting DTCDM OS, with relatively significant scores for both 1-27 mm and 28-65 mm, a finding supported by Nguyen et al (Nguyen et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…The results of one study confirm that patients with PTC with distant metastases have a good prognosis after treatment (Sampson et al, 2007). Another study found that sex is a prognostic factor for DTCDM, likely because estrogen production limits cancer progression (Suteau et al, 2021). The current study found that tumor size was an important factor affecting DTCDM OS, with relatively significant scores for both 1-27 mm and 28-65 mm, a finding supported by Nguyen et al (Nguyen et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Although thyroid cancer was diagnosed less frequently in male patients, we observed a higher rate of mortality from nearly all causes in male patients with thyroid malignancy in this study. Studies have demonstrated that thyroid malignancy characteristically presents at a more advanced stage and there is a worse tumor prognosis in males ( 46 , 47 ). Research on the influence of sex hormones on thyroid malignancy has continued to be inconclusive, while plenty of experimental research studies have indicated that estrogen and other hormones and their receptors may lead to tumorigenesis and tumor progression ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women are traditionally more keen on undergoing routine clinical examination along their lives as compared to men ( 27 , 28 ), which could be part of the reasons why thyroid nodules and cancers are more frequently detected in the female population. However, another studies showed that male gender was the clinical factor associated with the high risk of TC ( 16 , 29 ). Our results showed that the number of TC was more in male than in female, and gender was an independent risk factor associated with TC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, clinicians estimate the risk of TNs and make subsequent decisions based on comprehensive information including clinical and US findings ( 3 , 16 , 17 ). The existing RSSs are limited to B-mode US features and do not address clinical, Color Doppler and elastographic US characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation